Band gap engineering and modifying surface of TiO2 nanostructures by Fe2O3 for enhanced-performance of dye sensitized solar cell - Kilic, Bayram; Gedik, Nebi; Mucur, Selin Piravadilh; Hergul, Ahmet Serhan; Gur, Emre (Elsevier Sci Ltd, 2015)
Well-crystallized Fe2O3-modified TiO2 nanoparticles are prepared by a hydrothermal method and were successfully used as the photoanode of dye-sensitized solar cell (DSSC). Structural, optical and thermal characterizations were carried out by SEM, XRD, AFM, EDAX, DTG, TG and UV-vis spectroscopy. We show that the solar conversion efficiency, incident photocurrent efficiency (IPCE) and fill factor (FF) of Fe2O3-modified TiO2 are significantly increased, about 40%, compared those of to bare TiO2. DSSC shows power conversion efficiency of 7.27% based on Fe2O3-modified TiO2 while TiO2 anatase shows 5.10% solar conversion efficiency. The high improvement in cell performance is attributed to the enhanced light harvesting and high specific surface area for adsorbing more dye molecules in Fe2O3-modified TiO2 nanostructures. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dye sensitized solar cell; Fe2O3-modified TiO2; Nanostructures; Hydrothermal method